Digital Supply Chain Model for the Cargos Maritime Transport Management in Thailand - Chansamut, Artaphon (International Journal of Supply Chain Management, 2023)
The aim of this paper is to study and to assess digital supply chain model for the cargos maritime transport management in Thailand. A samples are ten experts in the field of information and supply chain. The data is analysed by means and standardized deviations. The paper consists of seven elements namely main elements Shipper, Port Operator, Freight forwarders , Suppliers ,Customers and Satisfaction. The assessment about digital model in supply chain for the cargos maritime transport management in Thailand using Black-Box technique. The research findings revealed that digital model in supply chain for the cargos maritime transport management in Thailand is appropriate at the high level , the ten experts agreed.